Synthesis and photophysical properties of metal free, titanium, magnesium and zinc phthalocyanines substituted with a single carboxyl and hexylthio groups - Canlica, Mevlude; Nyokong, Tebello (PERGAMON-ELSEVIER SCIENCE LTD, 2011)
2,3,9,10,16,17,23,24-Octakis( hexylthio)phthalocyanines (4a-6a) and 2-carboxy-9,10,16,17,23,24-hexakis( hexylthio)phthalocyanines (4b-6b) were synthesized using a one-pot method by cyclotetramerization of the phthalonitriles: 4,5-bis(hexylthio)phthalonitrile and carboxylic acid phthalonitrile. 2-Carboxycatecholato-2,3,9,10,16,17,23,24-octakis( hexylthio)phthalocyaninatotitanium(IV) (8) was prepared from 2,3,9,10,16,17,23,24-octakis(hexylthio)phthalocyaninatooxotitanium(IV) (7). The structures of these compounds were characterized by using elemental analyses, UV-Vis, FT-IR, H-1 NMR and mass spectroscopies. Their photophysical properties were also studied. The Phi(F) values are 0.12, 0.02, 0.10, 0.06, 0.10, 0.06, 0.65, 0.80 and the Phi(T) values are 0.58, 0.56, 0.57, 0.64, 0.22, 0.48, 0.17, 0.12 for 4-8, respectively. The Phi(F) value for complex 8 is higher than ever reported for phthalocyanine complexes. The triplet lifetimes (tau(T)) values for all the complexes were generally good, ranging from 50 to 310 mu s, and generally increased in the presence of the single carboxyl group. These complexes showed reasonable triplet quantum yields and lifetimes, and hence have potential for use as photosensitizers in photodynamic therapy (PDT) of cancer. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Photodynamic therapy; Titanium phthalocyanine; Triplet quantum yield; Unsymmetric phthalocyanine; Single carboxyl group; PHOTOCHEMICAL PROPERTIES; QUANTUM YIELDS; COMPLEXES; OXYGEN; TITANYLPHTHALOCYANINES; DERIVATIVES; WELL; Chemistry; Crystallography